A saxitoxin-binding aptamer with higher affinity and inhibitory activity optimized by rational site-directed mutagenesis and truncation. (July 2015) - Zheng, X.; Hu, B.; Gao, S.X.; Liu, D.J.; Sun, M.J.; Jiao, B.H.; Wang, L.H.
Abstract: Saxitoxin (STX), a member of the family of paralytic shellfish poisoning toxins, poses toxicological and ecotoxicological risks. To develop an analytical recognition element for STX, a DNA aptamer (APT STX1 ) was previously discovered via an iterative process known as Systematic Evolution of Ligands by Exponential Enrichment (SELEX) by Handy et al. Our study focused on generating an improved aptamer based on APT STX1 through rational site-directed mutation and truncation. In this study, we generated the aptamer, M-30f, with a 30-fold higher affinity for STX compared with APT STX1 . The Kd value for M-30f was 133 nM, which was calculated by Bio-Layer Interferometry. After optimization, we detected and compared the interaction of STX with aptamers (APT STX1 or M-30f) through several techniques (ELISA, cell bioassay, and mouse bioassay). Both aptamers' STX-binding ability was demonstrated in all three methods. Moreover, M-30f performs better than its parent sequence with higher suppressive activity against STX. As a molecular recognition element, M-30f has good prospects for practical application. Highlights: We obtain an aptamer with higher affinity and better inhibitory activity towards saxitoxin than parent sequence. We develop a feasible strategy to optimize aptamers characterized by SELEX process. No reported studies have measured the interaction between aptamers and small molecules using Bio-Layer Interferometry. We adopt ultrafiltration method to obtain free saxitoxin after interaction with aptamers.